2020
DOI: 10.1136/annrheumdis-2020-216963
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α regulates autophagy to promote fibroblast activation and tissue fibrosis

Abstract: ObjectivesCoactivators are a heterogeneous family of transcriptional regulators that are essential for modulation of transcriptional outcomes and fine-tune numerous cellular processes. The aim of the present study was to evaluate the role of the coactivator peroxisome proliferator-activated receptor gamma coactivator-1α (PGC-1α) in the pathogenesis of systemic sclerosis (SSc).MethodsExpression of PGC-1α was analysed by real-time PCR, western blot and immunofluorescence. Modulation of autophagy was analysed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…We observed that fibroblast-specific deletion of the autophagic gene Atg5 effectively reduced cardiac fibrosis in a mouse model of cardiac hypertrophy. In line with our data, knock-out of autophagy activator peroxisome proliferator-activated receptor gamma coactivator-1α in fibroblasts prevented development of skin fibrosis in a mouse model of systemic sclerosis [25]. The profibrotic role of autophagy in fibroblasts was further supported by in vitro data.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We observed that fibroblast-specific deletion of the autophagic gene Atg5 effectively reduced cardiac fibrosis in a mouse model of cardiac hypertrophy. In line with our data, knock-out of autophagy activator peroxisome proliferator-activated receptor gamma coactivator-1α in fibroblasts prevented development of skin fibrosis in a mouse model of systemic sclerosis [25]. The profibrotic role of autophagy in fibroblasts was further supported by in vitro data.…”
Section: Discussionsupporting
confidence: 88%
“…Here, we demonstrated a novel mechanism, by which the TGF-β-Fosl-2 axis regulated profibrotic changes in cardiac fibroblasts by activating autophagocytosis. Previous studies have already shown the significance of autophagy in promoting fibrotic processes in multiple organs including skin [25], lung [26], liver [27], kidney [28] and heart [9][10][11]. It should be noted that in the heart, autophagocytosis might also be involved in antifibrotic and cardioprotective processes [8,12,13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“… 19 PGC-1α promotes autophagy to foster TGF β-induced fibroblast activation. 20 So the fibroblast between muscles is less in siPGC-1α rat than in the wild type rat in the muscle images. The overexpression of PGC-lα and PGC-lβ may inhibit the expression of skeletal muscle-specific ubiquitin ligase, resisting denervated muscle shrinkage.…”
Section: Discussionmentioning
confidence: 95%
“… 25 , 26 So we find that the downregulation of PGC-1α level has more severe muscle atrophy in siPGC-1αgroup and primary molecular mechanism contributes to enhanced transcription of atrophy-related Atrogin-1 FoxO3 or NF-κB activation, and protein loss. 19 , 20 However, both long-term and acute exercise increases PGC-1α expression. 22 , 27 , 28 It enhances mitochondrial synthesis, and oxidative phosphorylation stimulates peroxisome proliferator-activated receptor (PPAR) to enable farnesoid X receptor (FXR) gene transcription, which promotes fat metabolism and prevents the incidence of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%